LIMITASI INFORMASI PUBLIK YANG DIKECUALIKAN TERHADAP PENGANUGERAHAN TANDA KEHORMATAN BINTANG JASA BAGI TERDUGA PELANGGAR HAM - Kusworo, Daffa Ladro (Jurnal Yuridis, 2024)
The development of public information disclosure disputes in the realm of the State Administrative Court has been polemic. Relaxation in interpreting exempted information is not clearly specified for the awarding of the title of honorary star of merit, one of which is in Decision Number: 541/G/KI/2023/PTUN.JKT that Joko Widodo awarded an honorary star to Erico Guetteres who has a bad record on human rights (HAM) in 2021. The impropriety of the award through Presidential Decree Number 78 / TK / 2021 is in fact seen from the track record of his crimes in East Timor in 1999. The Ministry of State Secretariat feels that its institution as a public body has the authority to refuse the provision of information that is categorized as exempt from disclosure, one of which contains personal information based on Law Number 14 of 2008 concerning KIP. The Ministry of State Secretariat challenged the opinion of the Panel of Commissioners, which did not pay attention to the personal data of Erico Guetteres and other title recipients. The research method refers to doctrinal which examines the applicable laws and regulations as well as paradigmatic information as the times evolve. The results show that the interpretation of exempted information is not fully standardized due to too many public information rules that are definitively still sectoral. Disharmonization is related to the view of the decision to grant merit marks included in the authentic deed or the type that can be disseminated in the public, not to mention how the disclosure is whether it is only announced or only involves public participation.